2010
DOI: 10.1016/j.ejcts.2009.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Modified thromboelastography evaluation of platelet dysfunction in patients undergoing coronary artery surgery

Abstract: TEG with platelet mapping is able to predict excessive postoperative blood loss among patients who underwent CABG and recent anti-platelet therapy. The prevalence of non-responsiveness to anti-platelet therapy, including clopidogrel, is higher in patients undergoing coronary artery bypass grafting than in the general population. In this study, aspirin-induced platelet dysfunction did not influence postoperative blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 31 publications
1
56
0
Order By: Relevance
“…We did not find a difference in bleeding rates associated with aspirin use; however, our study was not designed or powered to examine this question. Previous studies have reported no increase in post-CPB bleeding related to aspirin [23,31,32], while others have demonstrated a trend to increased blood product usage in aspirin-treated patients [33]. It seems that the evidence implicating early graft occlusion following coronary artery surgery due to platelet hyper-reactivity favours keeping patients on aspirin if they were already on it [34][35][36][37], hence in agreement with our cardiac surgeons we elected to enrol these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not find a difference in bleeding rates associated with aspirin use; however, our study was not designed or powered to examine this question. Previous studies have reported no increase in post-CPB bleeding related to aspirin [23,31,32], while others have demonstrated a trend to increased blood product usage in aspirin-treated patients [33]. It seems that the evidence implicating early graft occlusion following coronary artery surgery due to platelet hyper-reactivity favours keeping patients on aspirin if they were already on it [34][35][36][37], hence in agreement with our cardiac surgeons we elected to enrol these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Preisman et al examined the role of pre-operative platelet mapping in predicting bleeding tendency in patients on recent anti-platelet therapy (aspirin alone or aspirin and clopidogrel) undergoing coronary artery bypass surgery [23]. In this setting, clopidogrel-induced platelet dysfunction using ADP was able to differentiate between patients with or without excessive bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although revealed with different assay, study described the same phenomenon as we did. Using modified TEG with arachidonic acid as platelet agonist Preisman S et al showed 44% rate of non-responsiveness to aspirin [32]. Using the turbidimetric method for platelet aggregation measuring, Kempfert et al reported 28.8% patients with RPR before CABG.…”
Section: Antiplatelet Therapy Managementmentioning
confidence: 99%
“…1,5,7 Both standard hemostatic assessments (e.g., prothrombin time, fibrinogen concentration) and viscoelastic measurements of hemostasis (e.g., thromboelastometry, thrombelastography) have been used separately and in combination to predict post-CPB bleeding. [1][2][3]7,8 However, the tacit assumption that these laboratory methods could measure changes in plasmatic/platelet-mediated hemostasis that could be linked to remote bleeding events has not been supported.…”
mentioning
confidence: 98%